Diffusion of Cryptocurrency Among Arab Adopters: How Are Digital Technostress, Ethical Concerns, and Government Regulations Interconnected? - Abed Alnaser Nazmi N. Daana; Figen Yeşilada (SAGE Open)
This current study explores the intention to adopt cryptocurrencies (IACR) within the Arab world. The study is founded on the diffusion of innovation theory and examines the relationship through the mediation of digital technostress and the moderation of ethical issues and government regulations. The study employed a quantitative approach and gathered cross-sectional data from 437 respondents through an online survey. Subsequently, structural equation modeling (SEM) was utilized to test hypotheses. The findings indicated that digital technostress acts as a mediating factor in the relationship between variables such as complexity, observability, compatibility, and the intention to adopt cryptocurrency, while no mediating effect was observed between relative advantage and trialability and the intention to adopt cryptocurrency through digital technostress. Furthermore, the study confirmed the moderating role of ethical issues in the relationship between digital technostress and the intention to adopt cryptocurrency. However, no moderating effects of government regulations on cryptocurrency adoption among Arab investors were identified. Findings highlight the importance of fostering supportive regulatory environments for cryptocurrency investment in the Arab world and affirm the applicability of the diffusion of innovation theory in the context of blockchain and cryptography. Empirical evidence emphasizes the need for further longitudinal investigations in global regions.